Estimating LOC for OMA primitives: an approach based on correlation and regression analysis - Dilorenzo, Ednaldo; Furtado, Felipe; Silva, Mauro; Morais, Elisabeth; Aquino, Gibeon (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2008)
Estimating API size is a very complex work since no approaches address particularly this development unit. Existing approaches are concentrated in estimating the software as a whole. Since many projects need to estimate API size, analyzing previous development is extremely necessary in order to identify which variables lead the API size and this can bring managers to derive cost and effort from it. This paper presents a case study from a OMA protocol client project where those variables were identified and the correlation and multiple regression techniques were used to find a equation that can predict the size of development of API modules for this specific project in Lines Of Code (LOC) unit size.